Novel insights and clinical perception of the patients with acute leukemia transferred to ICU: a multi-center retrospective study spanning 10 years - Guo, Qicai; Liu, Yanquan; Chen, Xiaojun; Shen, Jianzhen; Li, Zuotao; Zeng, Minjuan; Yin, Yue; Xie, Jiachen; Li, Ye; Guo, Huidong; Cao, Zuohong (Frontiers in Medicine, 2025)
BackgroundIntensive care unit (ICU) is a professional and special ward for the treatment of various critical and severe diseases in clinical medical institutions, which is an important embodiment of the strength of critical and severe treatment in a hospital. Acute leukemia (AL) is one of the most common hematological malignancies with the most serious condition and poor prognosis. Different from other hematological malignancies, AL kills many young patients every year, although the treatment for AL has been perfected and put into clinical treatment for many years, however, due to the severity and rapid progression of AL, it is still necessary to strengthen the ability of nursing and medical treatment. Careful analysis and discussion of the rescue treatment and nursing of AL patients transferred to ICU is particularly necessary to improve the rescue ability of malignant hematological tumors in the critical stage and improve the rescue success rate of AL.ObjectiveThe purpose of this paper is to discuss and analyze the clinical features, diagnosis, treatment and prognosis of AL patients transferred to ICU, so as to provide suggestions for improving the ability to treat malignant hematological tumors in critical stage and improve the rescue measures for AL. More importantly, our aim was to provide evidence-based insights for early warning systems and multidisciplinary approaches in managing critically ill patients with hematological malignancies, investigate the clinical characteristics and prognostic factors of AL patients requiring ICU admission, providing valuable insights for improving diagnosis, nursing, prognosis assessment, and palliative care in hematology and critical care medicine.MethodsClinical data were retrospectively collected and systematically organized for AL patients transferred to the ICU from the First Affiliated Hospital of Gannan Medical University, Fujian Medical University Union Hospital, the Affiliated Hospital of Putian University, and the Affiliated Hospital of Guangdong Medical University during January 2014 to January 2025. The collected data included general patient characteristics, age at onset, treatment regimens, routine hematological indicators, cytogenetic and molecular biological abnormalities, extramedullary organ infiltration, and acute physiology and chronic health evaluation scores (APACHE II score), ICU duration and outcomes, reasons for ICU admission, treatment courses during ICU stays, and relevant laboratory and imaging findings. This study aimed to analyze and discuss the clinical features, diagnostic and therapeutic approaches, and prognosis of leukemia patients admitted to the ICU.ResultsA total of 357 AL patients, aged 16.5 ~ 77 years, were included in this study, comprising 216 males and 141 females. The time interval from AL diagnosis to ICU admission ranged from 0.03 to 144 months, with a median of 1 month. The length of ICU stay varied between 1 and 30 days. From the perspective of the unique molecular biology and cytogenetics of AL, we found FLTS-ITD was independent risk factors for mortality of AML, while E2A-PBX1 and DNMT3A were independent risk factors for mortality of ALL. Regardless of whether the subtype of AL patients included in this study was AML or ALL, patients with complex karyotypes accounted for the largest proportion. Meanwhile, age, leukemia type, heart failure, APACHE II score, WBC, PLT, LDH, PCT, APTT significantly affected the time from diagnosis to transfer to the ICU in AL patients (p < 0.05), accompanied by the gene mutation of WT1, FLT3-ITD, and TP53 significantly affected the time from diagnosis to transfer to the ICU in AML patients (p < 0.05), and FLT3-ITD, E2A-PBX1, DNMT3A, HOX11, RUNX1 significantly affected the time from diagnosis to transfer to the ICU in ALL patients (p < 0.05). Univariate analysis revealed that heart failure, sepsis, continuous renal replacement therapy (CRRT), administration of two or more treatments simultaneously, APACHE II score ≥20, and procalcitonin (PCT) levels were significantly associated with prognosis. Multivariate analysis indicated that heart failure, CRRT, and APACHE II score ≥20 were independent risk factors for mortality. COX univariate analysis suggested that heart failure, vasopressor use, and APACHE II score were influencing factors for overall survival (OS), while multivariate analysis confirmed that vasopressor use was an independent risk factor for OS.ConclusionThe prognosis and outcomes for AL patients transferred to the ICU were generally poor. Some molecular biological and cytogenetic indicators can be used as early warning indicators for AL patients’ transfer to the ICU or short-term death. Acute respiratory failure, sepsis, and severe infections were the primary reasons for ICU admission. Heart failure, CRRT, and APACHE II score ≥20 were identified as independent risk factors for mortality, while vasopressor use was an independent risk factor for OS.